« first day (2273 days earlier)      last day (3042 days later) » 

14:04
Any hints on how to solve $\phi '''(t) + \phi(t) = 0$?
@Lozansky solve $m^3+1=0$
Ah right
finished all my midterms thank fuck
algebra was today and dear god algebra is hard
Analysis exam down
congrats! :)
14:24
@DHMO that works if you do an appropriate substitution first
@Semiclassical what do you mean?
well, $\phi(t)$ isn't m^3, is it?
have to assume that the solution is of a particular form to get that
(it is, of course, but one has to do $\phi(t)=e^{i m t}$)
@Semiclassical isn't that the auxiliary equation?
yeah, but one should presumably understand where that comes from :/
and not just say "hey, auxillary equation"
@Semiclassical so you are saying that every time we want to use auxiliary equation we have to prove it first?
14:27
if you're doing a course on it, probably yes
if you can just eyeball it in actual practice, fine
The problem was $\phi '(t) + \int_{0}^{t} (t-\xi) \phi(\xi) d \xi = t, \: \phi(0) =0$
but if you're doing an exam then probably it's worth taking the time to say "$\phi(t)=e^{i m t}$"
@Semiclassical no, you don't need to assume that
to get to the auxiliary equation?
14:29
What do you mean?
(probably simpler to do e^{m t} instead but that's hardly different)
Look, let's solve the equation $y''-y=0$
what the heck is an auxiliary equation
without ever assuming that $y=e^{mt}$
$y'' - y = 0$
$y'' - y' + y' - y = 0$
@0celo7 What you get when you plug an exponential ansatz into a linear ODE.
14:30
I got $\phi(t) = c_1e^{-t}+e^{t/2}(c_2 cos \sqrt{3}/2 t + c_3 sin \sqrt{3}/2 t)$
You mean a characteristic equation?
same thing, yeah
Just me, or won't it be pretty terrible to solve that for $c_1, c_2, c_3$?
@Lozansky Probably easier to write it as $c_1 e^{-t}+c_2 e^{-\omega t}+c_3 e^{-\omega^2 t}$ where $\omega=e^{2\pi i/3}$ is a cubic root of unity.
then you can appeal to stuff like $1+\omega+\omega^2=0$
frikken algebra
how do roots of unity even work
14:33
yup
@0celo7 They just be rotaty arrowy things
@Semiclassical Maybe. Would probably simplify the integral at least
@0celo7 ...
$y'' - y = 0$
$y'' - y' + y' - y = 0$
$e^{-x}y'' - e^{-x}y' + e^{-x}y' - e^{-x}y = 0$
$(e^{-x}y')' + (e^{-x}y)' = 0$
$e^{-x}y' + e^{-x}y = C_1$
$e^{x}y' + e^{x}y = C_1e^{2x}$
$(e^{x}y)' = C_1e^{2x}$
$e^{x}y = C_2e^{2x} + C_3$
$y = C_2e^{x} + C_3e^{-x}$
$\omega^n-1=(\omega-1)(\omega^{n-1}+\omega^{n-2}+\cdots +1)$
14:34
@Semiclassical in which step did I assume that $y=e^{mx}$?
ffs
just because you can do it without it doesn't mean that's how you'd actually do it
@Krijn what does that mean?
@Semiclassical so how do you do it?
@DHMO interesting
@0celo7 You can rotate roots of $X^n - 1$ around
That's all
14:35
that seems hard
I assume a solution of the form $y=e^{m t}$. that would require $y''-y = (m^2-1)e^{m x}=0$
I like DHMO's way better
that has two roots, $m=\pm 1$, and those yield distinct solutions
so therefore $e^{x},e^{-x}$ form a basis of solutions
your solution is valid
but my solution needs no assumption
@Semiclassical My advisor has a library book checked out that I want. Is it ok to ask him for it?
14:37
Okay. How would your solution look for $\phi'''+\phi=0$, then
@Semiclassical similar
must i type it out?
maybe I'd just type a portion
$\phi''' - \phi = 0 \iff (\partial_t^3 -1)\phi =0$
now $\partial_t^3-1 = (\partial_t -1)(\partial_t - e^{i2\pi/3})(\partial_t - e^{i4\pi/3})$
If you're not willing to type it out, why would I use it as a technique?
@Semiclassical who said I'm not going to type it out?
@s.harp thanks
sigh
@0celo7 Can't hurt. If there's a specific passage you need, he can probably photocopy it
14:39
@Semiclassical I have a PDF already
I'll admit, I like that arrangement if I was going to do something like $\phi'''-\phi = \Psi$
I want to read the first chapter or so and see if it's something I want to read more fully
$y'''-y=0$
$(y'''-y'')+(y''-y')+(y'-y)=0$
$e^{-x}(y'''-y'')+e^{-x}(y''-y')+e^{-x}(y'-y)=0$
$e^{-x}y''+e^{-x}y'+e^{-x}y=C_1$
$y''+y'+y=C_1e^x$
but I can't read that much on a pdf
this is the first part
14:40
sure. presumably you'd get two more similar parts
...or you could do $y=e^{m x}$, and not worry about cleverness
that gives $m^3=1$ immediately
somehow we went from $y'''+y=0$ to $y'''-y=0$. probably a typo on my part.
@Semiclassical cleverness? I kind of use the same approach for everything
@Semiclassical That kind of ansatz argument always bother me. I realize most people are ok with it if they want to know some specific solutions; but eh.
If you can guess an answer, and show that it works, then it's perfectly satisfactory.
Ansatz arguments are beautiful
How do you know if there aren't any other solutions?
14:43
Well, let me put it like this. Are you really telling me that you'd obtain the auxiliary equation by that chain of reasoning, that takes so long to write out that you don't want to do the whole thing?
@BalarkaSen Because it's a linear ODE
That's the kind of question I usually have in mind.
Now, if you're doing nonlinear stuff, then yeah
ansatz arguments are a bad idea in that case
@Semiclassical then how are you going to do $y''-2y'+y=0$?
Sure, it's a very specific approach, is all what I was saying.
In that particular case, I wouldn't want to use my approach. But it's hardly strange to use a different approach when the general one fails.
14:46
@Semiclassical i'm really curious. how would you do it?
Probably I'd do something like $y=ze^{x}$, since the auxiliary equation $m^2-2m+1=0$ has a double root at $m=1$
yeah isn't that what you do for Cauchy-Euler or one of those guys?
$xe^x$ or something
That gives $(z''+2z'+z)e^x-2(z'+z)+ze^x=z'' e^x=0$, so $z=C_1 x+C_2$
Isn't that $x^2y''+axy'+by=0$?
$y''-2y'+y=0$
$(y''-y')-(y'-y)=0$
$e^{-x}(y''-y')-e^{-x}(y'-y)=0$
$e^{-x}y'-e^{-x}y=C_1$
$e^{-x}y=C_1x + C_2$
$y=C_1xe^{x} + C_2e^{x}$
14:51
The other way to go at this, of course, is some sort of transform method
Though for that I'd want to be doing $Ly=f$ not $Ly=0$
@DHMO myself I'd put another line between the third and fourth steps, explicitly stating that $\frac{d}{dx}[e^{-x}(y''-y')-e^{-x}(y'-y)]=0$
@Semiclassical fair point
admittedly, things are going to get hairy whatever you do if you're doing something third-order or worse
e.g. $(D-1)^2(D+1)y=0$
what is that?
$D=\frac{d}{dx}$
What does $(D+1)$ mean?
14:55
$(D+1)y=Dy+y=y'+y$
wow, notation
but you already factored it for me
yeah.
if it's in factored form, then I can see the advantage of the direction integration route
e.g. $e^{x}(D+1)y=D(e^{x}y)$
actually that's just integrating factors
well, I mean that the next step would be $D(e^x y)=0\implies e^x y=C$
i.e. direct integration
sure
14:59
but, i mean, if someone gives me an ODE like $ay'''+by''+cy'+d=0$
i'm going to go directly to the $y=e^{m x}$ ansatz and see if I get distinct roots
if I do, I'm done.
if not, then more labor is required.
Look, we are both using auxiliary equations
just that you assume $x^ne^{mx}$ while I do not
if you have a polynomial $P(\partial_t)\phi=0$ the best thing to do is find the roots of the polynomial and write the equation as $(\partial_t - z_1)^{n_1}\cdot...\cdot(\partial_t - z_m)^{n_m}$. You know that everything in the direct sum of the kernels of the operators $(\partial_t - z_i)^{n_i}$ is a solution and from Picard Lindelöf theorem you get that this solution space has the same dimension as the solution space of your equation
eh. my point is that if you've got something like $y'''-y=0$, then going directly to $y=e^{mx}$ seems far simpler
@Semiclassical no. you solve the auxiliary equation first, or else you won't know if you have repeated roots
15:02
lol sorry
If you try $y=e^{m x}$ and it works, you're done. but regardless, that gives you the auxiliary equation
otherwise you're just pulling an equation out of nowhere and saying "hey, this thing has repeated roots"
and I'd rather pull a generic solution form 'out of nowhere' than an arbitrary equation
fair point
I would say "consider the following equation..."
or even put it to the rough work
I think one could reasonably proceed as @s.harp did, and frame it instead in terms of "how do I write $Ly=0$ as $(D-z_1)...(D-z_m)y=0$"
I am not too familiar with that notation
For example, I can't see this without converting it to "normal" form:
It's handy, especially if you're the kind of person who likes operator methods
15:05
8 mins ago, by Semiclassical
e.g. $e^{x}(D+1)y=D(e^{x}y)$
$D(e^xy)=(De^x)y+e^x(Dy) = e^x y+e^x Dy = e^x(1+D)y$
you can also write it in the following rather cute way: $e^{-x} D e^x = D+1$
not very different from converting it to $e^xy+e^xy'$
and more generally $e^{-\lambda x}D e^{\lambda x}=D+\lambda$
thanks
which is something you should perhaps recognize, @0celo7: $x$ generates translations in momentum space :>
15:09
@Semiclassical how would you use that?
@Semiclassical what is $D$ here? $e^{-i d/dx}$ or something?
just $d/dx$
oh, I'm thinking about the finite translation version
you're talking about the infinitesimal generator?
yeah. i'm being a bit sloppy
@DHMO well, I already have: $0=(1+D)y=e^{-x}D e^x y=0\implies ye^x=C$
where that $D$ notation really becomes fun, though, is if you have inhomogeneous ODEs
for instance $y+y'=e^{2x}$
@Semiclassical sloppiness overload
@Semiclassical let me try
15:12
@Semiclassical what is even going on there?
$(1+D)y=e^{2x}$
$e^{-x}D(e^xy)=e^{2x}$
$D(e^xy)=e^{3x}$
$e^xy=\dfrac13e^{3x}+C$
$y=\dfrac13e^{2x}+Ce^{-x}$
oh, hmm
don't see why that's sloppy
seems clever to me
@0celo7 theorem:
5 mins ago, by Semiclassical
and more generally $e^{-\lambda x}D e^{\lambda x}=D+\lambda$
@DHMO yes yes
@0celo7 because you included $y$ in the $D$
15:14
the sloppiness was in regards to the finite translations vs. infinitesimal translations business
it is like saying that $fDg=Dfg$
since I don't remember the terminology correctly off the top of my head
I didn't really understand that comment
what do the exponentials have to do with momentum space
yeah
15:15
well, first, let's trade derivatives for momentum i.e. $p=-i D=-i\frac{d}{dx}$
sure
$Dy=\dfrac23e^{2x}-Ce^{-x}$
$(1+D)y=e^{2x}$
Perfect match
then the above statement becomes $e^{-\lambda x} p e^{\lambda x}=p-i\lambda$
@Semiclassical let me try this...
sure
15:16
21 mins ago, by Semiclassical
e.g. $(D-1)^2(D+1)y=0$
and if I write $q=i\lambda$, that becomes $e^{-i q x}p e^{i q x}=p-q$
sure
so that's served to translate $p$ by $q$
$p\mapsto p-q$. that's all I'm asserting.
15:17
what map is that?
$\hat{A}\mapsto e^{-i q x}\hat{A}e^{i q x}$
although that is really pretty sloppy. I think you're saying $e^{-iqx}p[e^{iqx}f]=(p-q)f$.
sure. but that's pretty common notation in physics.
you typically don't write the thing you're acting on, just the operators themselves
$(D-1)^2(D+1)y=0$
$(D-1)^2e^{-x}De^xy=0$
$e^{2x}D^2(e^{-3x}De^xy)=0$
$D^2(e^{-3x}De^xy)=0$
$D(e^{-3x}De^xy)=C_1$
$e^{-3x}De^xy=C_1x+C_2$
$De^xy=C_1xe^{3x}+C_2e^{3x}$
$e^xy=C_1\left(\dfrac13xe^{3x}+\dfrac19e^{3x}\right)+C_3e^{3x}$
$y=C_1\left(\dfrac13xe^{2x}+\dfrac19e^{2x}\right)+C_3e^{2x}$
15:19
I'm still not sure what you're trying to tell me...
Hello ! Greeting !
@Semiclassical @DHMO Hey !
Can anyone help me verify the solution?
$x$ generates a unitary transformation of $p$ s.t. $p\mapsto p-q$?
I guess I'd put the point like this: just as the momentum operator $\hat{p}$ is the generator of translations in position, so to is the position operator the generator of translations in momentum
@Mahmoud as-salaam
15:21
oh. i've also assumed $\hbar=1$ so that $p=-i(d/dx)$.
Are you Muslim @DHMO ? O.O
@Mahmoud no
@Semiclassical of course
as-salaam ??? @DHMO
the cute approach via $D$ for $(1+D)y=e^{2x}$, btw
15:22
@Mahmoud I thought "Mahmoud" is an Arabic name lol, seeing its resemblance to Mohammed
is to totally abuse notation :P
Yes it is @DHMO
9 mins ago, by DHMO
$(1+D)y=e^{2x}$
$e^{-x}D(e^xy)=e^{2x}$
$D(e^xy)=e^{3x}$
$e^xy=\dfrac13e^{3x}+C$
$y=\dfrac13e^{2x}+Ce^{-x}$
Poor notation
7 mins ago, by DHMO
$Dy=\dfrac23e^{2x}-Ce^{-x}$
$(1+D)y=e^{2x}$
Perfect match
15:22
محمود @DHMO
@Mahmoud and "hello" in arabic is "as-salaam"?
as-salaamo alaykom
sure
Which means May peace be upon you ! :)
السلام عليكم
@Mahmoud you're a muslim?
15:24
Ok just ignore me and continue with the problem I shouldn't have interrupted you.
Yes.
namely, $$(1+D)y=e^{2x}\implies y=(1+D)^{-1} e^{2x}= (1-D+D^2+\cdots)e^{2x} = (1-2+2^2+\cdots )e^{2x}=\frac{1}{1+2}e^{2x}=\frac{1}{3}e^{2x}$$
@Mahmoud there's no on-going problem here
@Mahmoud nice to know that
which looks totally absurd, but gives the correct particular solution
@Semiclassical what the hell?
That is the correct reaction, lol
15:25
but you forgot $Ce^{-x}$
Hence why I said particular solution
You can't get the homogeneous solution this way.
@Semiclassical $(1+D)y=e^{2x}\implies y=(1+D)^{-1} e^{2x}=\dfrac{1}{1+2}e^{2x}=\dfrac{1}{3}e^{2x}$
Lol
one absurdity less
That's more physics than I can handle
15:26
lol
To make that less absurd, you'd want to think of this in terms of some transform method
transform method?
I took the exam @Semiclassical
Laplace?
Laplace transforms, Fourier transforms, etc.
I'm only familiar with Laplace transform
15:28
ah.
Fourier transform is similar but not identical
There's probably some way of making that rigorous using pseudo differential operators or something
I know there are relations between them but I forget how
@Mahmoud Ah. How was it?
which transform should I use here?
Don't know, tbh.
I think Laplace would work here
let me try Laplace
15:29
Pretty straight forward but I couldn't solve the last problem. @Semiclassical
Okay. What was it asking?
Prove (As always :/) that :
What test?
$(1+D)y=e^{2x}$
$y+Dy=e^{2x}$
$F(s)+sF(s)-y(0)=\dfrac1{s-2}$
$(1+s)F(s)=\dfrac1{s-2}+C_1$
$F(s)=\dfrac1{(s-2)(s+1)}+\dfrac{C_1}{s+1}$
$F(s)=\dfrac{1/3}{s-2}-\dfrac{1/3}{s+1}+\dfrac{C_1}{s+1}$
$F(s)=\dfrac{1/3}{s-2}+\dfrac{C_2}{s+1}$
$y=\dfrac13e^{2x}+C_2e^{-x}$
works perfectly @Semiclassical
yeah
and in that case being able to divide by $(1+s)$ is perfectly legit
15:35
$$(a\neq b) \lor(b\neq c) \lor(a\neq c) \implies a^2+b^2+c^2\neq ab+bc+ac$$
@Semiclassical what do you mean?
God I hate Laplace transforms
@0celo7 with a passion?
Almost
I hate them less than linear algebra fwiw
Hmm
For that to hold, you need at least one of $a,b,c$ to be different than the others.
15:37
$(a\neq b) \lor(b\neq c) \lor(a\neq c)$
$\implies (a-b\ne0) \lor (b-c\ne0) \lor (a-c\ne0)$
$\implies ((a-b)^2>0) \lor ((b-c)^2>0) \lor ((a-c)^2>0)$
$\implies (a-b)^2 + (b-c)^2 + (a-c)^2 > 0$
$\implies 2a^2+2b^2+2c^2 - 2ab-2bc-2ac > 0$
$\implies a^2+b^2+c^2 - ab-bc-ac > 0$
$\implies a^2+b^2+c^2 > ab-bc-ac$
$\implies a^2+b^2+c^2 \ne ab-bc-ac$
in fact, all of the $\implies$ can be changed to $\iff$
@Semiclassical what does this mean?
oh, I just meant that when I wrote $(1+D)y=f\implies y=(1+D)^{-1} f$ it's rather absurd on the face of it
on the other hand, you also get something like $(1+s)Y=F$ at the level of the Laplace transform
Green's functions.
I see
and in that case it's perfeclty valid to move $(1+s)$ to the other side.
If only one of them is different, then you'd have (without loss of generality) $a=b\neq c$, which would require $2a^2+c^2 \neq a^2+2ac\implies (a-c)^2\neq 0$ which is always true.
so the only case that needs be considered is $a\neq b\neq c\neq a$
but I like DHMO's approach.
@Semiclassical thanks
15:43
it basically amounts to rewriting the desired condition as $(a-b)^2+(b-c)^2+(c-a)^2\neq 0$, which is only false when all three are equal.
I'm back sorry.
Find number of different tree with 8 nodes?

http://math.stackexchange.com/questions/1983008/number-of-different-trees-with-8-nodes
@Mahmoud as-salaam alaykum
:) @DHMO
@DHMO ,Wa-Alaikum-Salaam :)
15:47
Wa alaykum as-salaam =) @DHMO
@MithleshUpadhyay so many arabic xd
I bet noone here speaks my language
Russian is not very rare...
Not russian
15:48
@DHMO , you welcome, and Namastey ! :)
Ti govoris po russki, @DHMO?
@Lozansky I'm not Russian
I'm talking about swedish
@MithleshUpadhyay I've seen your question however you need to know the question is whether is about labeled or unlabeled tree
@Lozansky Are you from Russia? where exactly?
Thanks @DHMO for your solution $$=-)$$
15:50
@YOUSEFY From the western part of Russia called Sweden ^^
@Mahmoud you are welcome
@YOUSEFY It should be labeled, rt?
@DHMO I had an interesting question on my complex analysis exam
@Lozansky Cam on you are not from Russia!!
@Lozansky what is it?
15:51
Is there any good lecture available on the Internet about Set Theory ?
@MithleshUpadhyay According to my knowledge, if the question doesn't specify, then we assume it is about unlabeled tree
@DHMO Find a conformal mapping $w=f(z)$ that maps $|z|<1$ to $|w|<1$ with $f(0)=1/2$
That sounds like a Blaschke product
@YOUSEFY Sorry to disappoint :(
@YOUSEFY , ok , thanks
15:54
@Semiclassical What do you think ?
on the question you asked?
I like DHMO's solution; i think it's nicer than what I could've come up with
@Semiclassical I don't know what Blaschke product is
No about Set Theory.
@Lozansky what is a conformal mapping?
15:56
Okay thanks
From that, I get $z=\frac{w-1/2}{1-w/2}$ up to a multiplicative constant
which gives $w=f(z)=\frac{z+1/2}{1+z/2}$
@DHMO Basically a map that preserves angles
@Semiclassical That's cheating :P We don't know about Blaschke products

« first day (2273 days earlier)      last day (3042 days later) »